pPHI: Path Validation for a Lightweight Anonymity Protocol - Kochiyama, Mio; Yoshinaka, Yutaro; Takemasa, Junji; Koizumi, Yuki; Hasegawa, Toru (Proceedings - International Conference on Network Protocols, 2025)
Lightweight anonymity protocols provide a well-balanced anonymity and performance by encrypting and decrypting only packet headers under the active and local adversary threat model. Among them, PHI and dPHI are promising in universally providing relationship anonymity. However, when overlaid onto IP, they are susceptible to the router skipping attack, where honest routers are skipped by malicious routers. Although this attack poses a significant threat to anonymity, its prevention is challenging due to the lack of path integrity in these protocols. To address this limitation, this paper integrates path validation into dPHI. This integration is non-trivial, as anonymity and path validation are inherently contradictory requirements. This paper designs and implements pPHI, a novel protocol, and analyzes pPHI in terms of security and performance.